2012
DOI: 10.1371/journal.pone.0033481
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Helicobacter pylori Shikimate Kinase Reveal a Selective Inhibitor-Induced-Fit Mechanism

Abstract: Shikimate kinase (SK), which catalyzes the specific phosphorylation of the 3-hydroxyl group of shikimic acid in the presence of ATP, is the enzyme in the fifth step of the shikimate pathway for biosynthesis of aromatic amino acids. This pathway is present in bacteria, fungi, and plants but absent in mammals and therefore represents an attractive target pathway for the development of new antimicrobial agents, herbicides, and antiparasitic agents. Here we investigated the detailed structure–activity relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…A site-directed mutagenesis study on SDH of Escherichia coli showed that it lost substrate-binding activity when the residues were mutated at positions 67, 92, and 107 (T65, J69, and D105, respectively in SDH of H. pylori ) [30]. Our previous study also showed that mutations in the pathway anchor residues (M10, S12, S15, D33, F48, R57, and R132 in SK) reduced the activity of shikimate kinase [14], [31]. These results suggest that the pathway anchors are essential for catalytic reactions and that the mutations on the pathway anchor resides often decrease enzyme activities of SDH and SK (Figs.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…A site-directed mutagenesis study on SDH of Escherichia coli showed that it lost substrate-binding activity when the residues were mutated at positions 67, 92, and 107 (T65, J69, and D105, respectively in SDH of H. pylori ) [30]. Our previous study also showed that mutations in the pathway anchor residues (M10, S12, S15, D33, F48, R57, and R132 in SK) reduced the activity of shikimate kinase [14], [31]. These results suggest that the pathway anchors are essential for catalytic reactions and that the mutations on the pathway anchor resides often decrease enzyme activities of SDH and SK (Figs.…”
Section: Resultsmentioning
confidence: 96%
“…Diagrams of the ligands and the pathway anchors for (C) SDH and (D) SK. Residues are colored in red if their mutations lead to loss of enzyme activity [14], [19], [30], [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al also identified the naphthalene-2-sulfonate 25, which had an IC 50 value of 4.9 µM (Fig. 4) [29]. The authors also solved the crystal structure of E114A Hp-SK variant enzyme in complex with 25 (PDB entry 3N2E, 2.53 Å) (Fig.…”
Section: Inhibitors Identified By Screeningmentioning
confidence: 97%
“…Bearing in mind the fact that the elimination mechanism of the DHQ2 enzymes proceeds via enol intermediate 26, which is characterized by ring-flattening between the C2-C3 bond, Frederickson et al [51] designed the first mimetic of the enolate intermediate, 2,3-dehydroquinic acid (29), which proved to be a reversible competitive inhibitor of Mt-DHQ2 and Sc-DHQ2 with K i values of 200 µM and 30 µM, respectively (Fig. 9).…”
Section: Enolate Intermediate Mimeticsmentioning
confidence: 99%